The Effect of Audiovisual and Demonstration Towards Students Swimming Ability of Navy’s Cadets - Angga Teguh Prasetiyo; Yoso Wiyarno; Rufi'i Rufi'i (Journal of Education and Teaching (JET), 2024)
This study investigates the learning outcomes of Navy Cadets at Puslatdiksarmil in basic swimming, specifically breaststroke. A quantitative experimental design was used, involving 100 students divided into two groups: an experimental group receiving audiovisual and demonstration (AV-D) instruction and a control group with only demonstration (D). The performance test, based on the correctness of breaststroke technique, measured students' skills before and after treatment. A motivation questionnaire was also used to assess the impact of motivation on swimming ability. Results showed that the experimental group achieved a higher average score (73.16) compared to the control group (66.39). This indicates that AV-D significantly improves learning outcomes. Therefore, incorporating AV-D is recommended to enhance cadets' swimming abilities at Puslatdiksarmil.